PELAKSANAAN PELAYANAN SOSIAL PANTIJOMPO OLEH UNIT PELAKSANA TEKNIS (UPT) PANTI SOSIAL TRESNA WERDHA “KHUSNUL KHOTIMAH” DINAS SOSIAL PROVINSI RIAU TAHUN 2018 - Devi Monita; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The implementation of social services for nursing homes by UPT Social Services Tresna Werdha "KhusnulKhotimah" in 2018 faced problems, namely the condition of the guesthouse as a residence from the elderly requires renovations such as repainting, ceiling repairs, repair of drainage systems for bathrooms, and roof changes, the need to increase the knowledge of sports instructors and skills instructors, the absence of permanent doctors. Based on the description of the phenomena stated, the formulation of the problem in this research is how the implementation of social services for nursing homes by the Technical Implementation Unit (UPT) Tresna Werdha Social Services "Khusnul Khotimah" Social Service Riau Province in 2018? What are the factors that hinder the implementation of social services for nursing homes by the Technical Implementation Unit (UPT) of Tresna Werdha Social Services "Khusnul Khotimah" Social Service of Riau Province in 2018? Nursing home social services by the Technical Implementation Unit (UPT) Tresna Werdha Social Service "Khusnul Khotimah" Social Service of Riau Province in 2018, to find out the inhibiting factors of the implementation of nursing home social services by the Technical Implementation Unit (UPT) Tresna Werdha Social Services "Khusnul Khotimah" Riau Province Social Service in 2018. Primary data sources through interviews and secondary data sources. The data analysis technique was carried out with a qualitative descriptive analysis. The implementation of nursing home social services by the Technical Implementation Unit (UPT) of the Tresna Werdha "Khusnul Khotimah" Social Service of Riau Province in 2018, has leadership characteristics that are service vision, high standards are still not met and are not in-the field leadership style, and because responsive, then it is considered to have integrity. Employees serving have been fulfilled, exchanging information has been running, facilities and infrastructure are sufficient but need renovation, handling complaints is by replacing damaged equipment if there is still a backup, quickly repairing if there is damage to the facility even though temporary, inhibiting factors are bureaucracy, limited human resources, some facilities and infrastructure in conditions that are not optimal.Keywords: Implementation, service